Criptococose: padrões de mortalidade no Brasil e morbimortalidade em hospital de referência do Ceará - Oliveira, Aline Silva de (2018)
Cryptococcosis is a disease of global distribution and impact caused by Cryptococcus genus fungi. The disease greatest occurrence occurs in people with natural immunosuppression, however, it can also occur in immunocompetent people. In Brazil, there is no compulsory notification for this disease, so, there is no reliable database for measuring the morbidity and mortality magnitude in the country. Most clinical epidemiological studies are focused on South and Southeast regions, and the results can’t be generalized throughout the country. In this way, this study aims to characterize the mortality related to cryptococcosis in Brazil and the morbidity and mortality patterns of the disease in a Ceará’s reference hospital. The study was divided into two stages: 1. Ecological study of temporal trend and spatial analysis of cryptococcosis-related deaths in Brazil; and 2. A cross-sectional study with cases of cryptococcosis in patients treated at Hospital São José. In stage 1, the time trend was performed with regression analysis by inflection points (joinpoint), and the presence of spatial autocorrelation was verified using the index spatial association (LISA). In stage 2, the records of cases of cryptococcosis treated in the period from 2005 to 2016 were reviewed and epidemiological, clinical and laboratory factors were investigated. Statistical analysis was performed using Stata software version 11.2. There was a tendency to reduce the mortality coefficient in the Southeast regions (annual percentage change [APC] = -4.2 *), South (APC = -0.4) and Center-West (APC = -0.3). Regarding mortality related to cryptococcosis in Brazil, we observed a significant growth trend in the North (APC = 6.5 *) and Northeast (APC = 4.3 *), and the presence of high-high-density municipalities in the Southeast, South and Center-West, and high-low pattern in the North and Northeast. Relationed to cryptococcal morbidity and mortality pattern in Ceará, we observed a predominance of the disease occurrence in based immunosuppression people, mainly affected by HIV / AIDS, male, economically active age and living in the capital’s state. The most common clinical presentation of the disease was cryptococcal meningitis (39; 54.17%), followed by the disseminated form (12; 16.67%). The hospitalization time ranged from 3to 141 days with an average of 24 days. The cryptococcosis lethality rate in the period was 36.11%, with sequelae occurring in 24% of the patients who evolved to hospital discharge. The bivariate analysis showed a higher prevalence in the occurrence of deaths in the age groups of 40 to 59 years (prevalence ratio [RP] = 2.31, reliability interval [CI]: 1.13 -4.74) and in those older than 60 (RP = 4.63, CI: 2.74 -7.82, p- value [p] = 0.005), as well as people who underwent orotracheal intubation procedures (RP: 16.46; , 46-49.61, p <0.001), hemodialysis (RP: 4.57, CI: 2.87 -7.26, w: <0.001). In conclusion, we verified that mortality related to cryptococcosis in Brazil shows a tendency to decline, which may be related to the better survival and quality of life of people with HIV / Aids immunosuppression, transplanted and other conditions, since it wasn’t observed in the creation and / or implementation of specific policies or measures to control the disease. Related to the patterns or illness by cryptococcosis in Ceará, it’s observed that this one follows a similar patterns to that one described in literature in other regions of the country, in which occurs predominantly in males, in the economically active age group, and with based immunosuppression caused mainly by HIV / AIDS infection.